2005
DOI: 10.1590/s1678-91992005000100005
|View full text |Cite
|
Sign up to set email alerts
|

Snake envenomations in northwest counties of the Rio de Janeiro State, Brazil

Abstract: ABSTRACT:The frequency of envenoming in Northwest counties of the Rio de Janeiro State, Brazil, from 1995 to 2000 was evaluated. Reports from the Municipal Secretariat of Health of these counties were used. The results demonstrated that, from 1997 to 1999, there was a shortage of notification, and 40 cases of envenomations caused by Bothrops snakes were registered. These cases were more common from February to October, and the lower limbs of male peasants were the mainly affected areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
4
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
6
4
0
Order By: Relevance
“…This is not surprising, since snakes are more active during warm seasons. Also consistent with previous reports, in our study males (54.9%) and young adults (40%) were more affected by envenomations (5,13,14,(17)(18)(19)). An interesting observation in the current study was that almost all patients (95%) actively sought medical help and a significant fraction (43.3%) reached a healthcare facility in less than one hour after the bite, which indicates that the population is aware of the serious consequences of snake envenomations.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is not surprising, since snakes are more active during warm seasons. Also consistent with previous reports, in our study males (54.9%) and young adults (40%) were more affected by envenomations (5,13,14,(17)(18)(19)). An interesting observation in the current study was that almost all patients (95%) actively sought medical help and a significant fraction (43.3%) reached a healthcare facility in less than one hour after the bite, which indicates that the population is aware of the serious consequences of snake envenomations.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, other species from the Colubridae family were also classified as medically important in Turkey, such as Malpolon monspessulanus, Telescopus fallax and Telescopus nigriceps (6,(14)(15)(16). Corroborating the literature from several countries, we found that the frequency of snakebites is higher in warmer periods of the year, peaking in June (2,14,17,18). This is not surprising, since snakes are more active during warm seasons.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This seasonality factor agrees with several reports in the literature for many poisonous animals (12). The predominance of accidents in these months also occurs in southern, west central and central regions of the country (8,10).…”
Section: Introductionsupporting
confidence: 91%
“…In developing countries, accidents resulting from poisonous animals, including honeybees and caterpillars, are a serious health problem, due to the gravity of the wounds and the sequelae among the victims (12). The stings of honeybee and caterpillars may induce allergic reactions, causing great discomfort or even leading to death.…”
Section: Introductionmentioning
confidence: 99%